THE MODERATION ROLE OF FAMILY OWNERSHIP: THE INFLUENCE OF DIRECTORS CHARACTERISTICS ON THE LEVEL OF FINANCIAL RISK DISCLOSURE AND IMPLICATIONS FOR FINANCIAL PERFORMANCE: Empirical Study of the Banking Industry Listed on the Indonesian Stock Exchange - Surahman, Lira Amalia; Zulfikar, Rudi; Yulianto, Agus Sholikhan (International Journal of Multidisciplinary Research and Literature, 2025)
This study aims to examine the level of risk in disclosure practices and the impact of three board characteristics (director education, board size, and director age) on financial risk disclosure in the banking industry. This research also contributes to the literature by testing the moderating effect of family ownership on the relationship between board characteristics and company risk disclosure, as well as its implications for financial performance. The population in this study consists of banking industry companies listed on the Indonesia Stock Exchange for the period 2016-2023, using a purposive sampling method, resulting in 11 companies and a total sample of 88 observation data. The analysis techniques used include multiple regression analysis and MRA testing with SPSS 27 software. The results show that director education, board size, and director age have a positive effect on financial risk disclosure. The study also reveals that the moderating variable of family ownership strengthens the relationship between director education and financial risk disclosure. Conversely, family ownership moderation weakens the relationship between board size, director age, and financial risk disclosure. Furthermore, financial risk disclosure does not affect financial performance